ENHANCING RICE SEEDLING GROWTH WITH FE3O4 NANOPARTICLES: MITIGATING ARSENIC STRESS FOR SUSTAINABLE AGRICULTURE (The Research of Medical Science Review, 2025)
Arsenic contamination of soil presents a significant challenge to rice cultivation and food security globally. This study evaluates the effects of Fe3O4 nanoparticles on rice seedling growth kinetics under arsenic stress. Over a 7-day period, germination rates, shoot lengths, and root lengths were measured. The control group showed a 75% germination rate, with average shoot and root lengths of 1.06 cm and 41 cm, respectively. Treatment groups exposed to 10 ppm, 20 ppm, and 50 ppm Fe3O4 nanoparticles yielded germination rates of 41%, 66%, and 79%, and corresponding shoot lengths of 2.06 cm, 2.97 cm, and 3 cm, respectively. Root lengths were enhanced to 66 cm, 75 cm, and 79 cm at these respective concentrations. The findings indicate that Fe3O4 nanoparticles, particularly between 20 ppm to 50 ppm, promote the growth of rice seedlings without adverse effects even under arsenic stress. This advancement holds promise for improving sustainable agriculture and addressing arsenic-related food security concerns in affected regions, potentially leading to increased crop yields.